Best in snow [compact disc, unabridged] - Rosenfelt, David (Rosenfelt, David. Andy Carpenter novels., 2021)
"In this Christmas mystery, lawyer Andy Carpenter and his golden retriever, Tara, are on the beat after a body turns up in the snow and a journalist is the prime suspect"--